Arsenic and fluoride co-enrichment of groundwater in the loess areas and associated human health risks: A case study of Dali County in the Guanzhong Basin - Rui-ping Liu; Fei Liu; Hua-qing Chen; Yu-ting Yang; Hua Zhu; You-ning Xu; Jian-gang Jiao; Refaey M El-Wardany (China Geology, 2024)
ABSTRACT: This study aims to reveal the occurrence and origin of typical groundwater with high arsenic and fluoride concentrations in the loess area of the Guanzhong Basin—a Neogene faulted basin. Key findings are as follows: (1) Groundwater samples with high arsenic and fluoride concentrations collected from the loess area and the terraces of the Weihe River accounted for 26% and 30%, respectively, of the total samples, with primary hydrochemical type identified as HCO3-Na. The karst and sand areas exhibit relatively high groundwater quality, serving as preferred sources for water supply. It is recommended that local governments fully harness groundwater in these areas; (2) groundwater with high arsenic and fluoride concentrations in the loess area and the alluvial plain of rivers in Dali County is primarily distributed within the Guanzhong Basin, which represents the drainage zone of groundwater; (3) arsenic and fluoride in groundwater originate principally from natural and anthropogenic sources; (4) the human health risk assessments reveal that long-term intake of groundwater with high arsenic and fluoride concentrations pose cancer or non-cancer risks, which are more serious to kids compared to adults. This study provides a theoretical basis for the prevention and treatment of groundwater with high arsenic and fluoride concentrations in loess areas.